2012
DOI: 10.2203/dose-response.12-030.wiegant
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis and Cellular Quality Control: A Possible Explanation for the Molecular Mechanisms that Underlie the Benefits of Mild Stress

Abstract: ᮀ In contrast to the detrimental action of severe stress conditions, the beneficial effects of mild stress, known as hormesis, is increasingly discussed and studied. A variety of applications for hormesis in risk assessment processes, anti-ageing strategies and clinical therapies have been proposed. The molecular mechanisms underlying the phenomenon of hormesis, however, are not yet fully understood. A possible mechanism that has been proposed for hormesis, the homoeostasis overshoot hypothesis, assumes that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 91 publications
0
25
0
2
Order By: Relevance
“…It has also been suggested that an adaptive response to restore homoeostasis triggered by a moderate stress exposure may lead to an over‐correction with beneficial effects (eustress, hormesis) (Wiegant et al, ). In this work, we performed a transcriptional analysis of barley embryos after low‐dose and high‐dose gamma irradiations of seeds to reveal changes on gene expression programmes that may be responsible for growth stimulation and inhibition, respectively, at the later stages of ontogeny (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that an adaptive response to restore homoeostasis triggered by a moderate stress exposure may lead to an over‐correction with beneficial effects (eustress, hormesis) (Wiegant et al, ). In this work, we performed a transcriptional analysis of barley embryos after low‐dose and high‐dose gamma irradiations of seeds to reveal changes on gene expression programmes that may be responsible for growth stimulation and inhibition, respectively, at the later stages of ontogeny (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…pesticides, ozone and heavy metals). The stimulatory effects caused by the influence of either chemical or physical stressors are often originated in a similar way, involving the same molecular pathways, despite the fact that their damaging mechanisms are different (Wiegant, Poot, Boers-Trilles, & Schreij, 2013). These overlapping responses include the activation of heat-shock proteins, proteasomes, kinase cascades, and, in general, repair and antioxidant response processes (Tang & Loke, 2015;Wiegant et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stressinduced activation of transcription factors such as the Forkhead box O (FOXO), Heat Shock Factors (HSFs) and Hypoxia-Inducible Factors (HIFs), drives the expression of antioxidant enzymes and protein chaperones, to cope with protein misfolding and aggregation (6,7). Perhaps counterintuitively, exposure to a low dose of a harmful stressor can make an organism more resistant to higher and otherwise detrimental doses of the same stressor (8). The induction of improved stress tolerance, called hormesis, has been observed in response to oxidative stress, heat and radiation, in organisms ranging from microbes to plants to humans (9,10).…”
mentioning
confidence: 99%
“…This adaptive response to cellular stress, can even lead to lifespan extension and cross adaptation to other stress factors (11). Improved stress tolerance is thought to depend on protective activation of cytoprotective mechanisms that permit a more effective response to stronger environmental stressors (8). However, the concept of hormesis, and the nature of its underlying molecular mechanisms, remains contentious (12,13).…”
mentioning
confidence: 99%